Contribution of Prejudice to Shiitegroups on Student Tolerance - Dyah Rahmatika, Novia; Meiza, Asti; Kurniadewi, Elisa (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is a plural country, one of which is religion. The majority of Indonesian people embraced Islam. In Islam there are several sects that have different views in understanding Islam, one of them is the Shiite group. Today, Indonesians tend to view Shi’ism negatively. However, from the preliminary study of UIN SunanGunungDjati Bandung students, they tend to see Shiite positively. Researchers are interested to see whether prejudice contributes to the tolerance of UIN SunanGunungDjati Bandung students. This research uses quantitative method with data processing technique that is simple linear regression analysis. Data were collected using the Prejudice Scale and Tolerance Scale on 350 subjects. From the results of inferential analysis using a significant level of 1% indicates that prejudice affects the tolerance of UIN SunanGunungDjati Bandung students against the Shiite group. While the result of descriptive analysis indicates the subject is more at the level of prejudice that is and have a tolerance that is also.